2012
DOI: 10.1145/2185376.2185378
|View full text |Cite
|
Sign up to set email alerts
|

Desynchronization with an artificial force field for wireless networks

Abstract: Desynchronization is useful for scheduling nodes to perform tasks at different time. This property is desirable for resource sharing, TDMA scheduling, and collision avoiding. Inspired by robotic circular formation, we propose DWARF (Desynchronization With an ARtificial Force field), a novel technique for desynchronization in wireless networks. Each neighboring node has artificial forces to repel other nodes to perform tasks at different time phases. Nodes with closer time phases have stronger forces to repel e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…In DESYNC [6], for each period, a node adjusts its firing time towards a midpoint between two nodes that fire just before and just after itself to avoid a collision. DWARF [7] uses an algorithm inspired by robotic circular formation to create an artificial force field. The algorithm uses all neighbors' timing information to calculate the overall force acting on one node.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In DESYNC [6], for each period, a node adjusts its firing time towards a midpoint between two nodes that fire just before and just after itself to avoid a collision. DWARF [7] uses an algorithm inspired by robotic circular formation to create an artificial force field. The algorithm uses all neighbors' timing information to calculate the overall force acting on one node.…”
Section: Related Workmentioning
confidence: 99%
“…Based on only listening to neighbors' firing messages, desynchronization attempts to schedule nodes to perform tasks at different time. Previous works (e.g., DESYNC [6], DWARF *Corresponding author [7]) have shown that desynchronization successfully schedules nodes in static wireless networks. However, desynchronization in vehicular networks has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the concept of an artificial force fields, DWARF [5] achieves significantly less error than DESYNC by comparing phase difference with all neighbors to calculate proper phase adjustment. Degesys and Nagpal [6] also extend DESYNC to support multi-hop networks by reducing the desynchronization problem in to graph-coloring problem.…”
Section: Correlation Of Weight and Desynchronization Errormentioning
confidence: 99%
“…Nodes with correct phase differences(1,2,4,5) are tied-up and their weights are increased. Light nodes(3,6) can move whereas heavy nodes attempt to stay together.Algorithm 1 Initialization 1: T ← T imeP eriod {Configurable Time Period} 2: P GAP ← T /N umN eighbors {Perfect phase diff} 3: nextN brT ime, prevN brT ime, lastReceiveT ime ← 0 4: lastF iringT ime, bckwdW eight, fwdW eight ← 0 5: chaining ← BACKW ARD 6: call SetFiringTimer(T )…”
mentioning
confidence: 99%
“…Desynchronization is a primitive leading to fair time-division multiple access (TDMA) scheduling without requiring clock synchronization among sensors or a coordinating node [3,4,6,7,[9][10][11][12][13]. The key concept behind desynchronization is reactive listening, according to which, nodes periodically broadcast fire messages and then update their next broadcast time based on the reception of fire messages from other nodes.…”
Section: Introductionmentioning
confidence: 99%